Choose electronic materials for teaching and learning : some criteria to design web pages - Gil, Henrique (2011)
The increase of Web pages (school Web pages mainly) is considered as a positive factor in the Portuguese educational system. However many of these pages were developed chaotically, i. e. there were no criteria. Due to this situation, in spite of the increase of the number of sites the quality did not improve and a result is frustration among the users because their Web searches do not match their expectations. The present paper tries to show some results of recent research related to criteria that must be kept in mind when designing a Web page with quality.